Magnitude of neonatal sepsis and its associated factors among neonates admitted to the neonatal intensive care unit in Hawassa Comprehensive Specialized Hospital, Sidama Regional State, Ethiopia, 2020 - Frehiwot Sisay Baheru; Bisrat Zeleke Shiferaw; Tigistu Toru; Fisha Alebel GebreEyesus (BMC, 2024)
Abstract Background Neonatal sepsis is one of the most common causes of disease and death among neonates globally. And it made a great contribution to neonatal admission to intensive care units. To mitigate the ongoing neonatal crisis and accomplish the goal of sustainable development through a decrease in neonatal mortality, information from various regions is needed. Despite the considerable burden of neonatal sepsis in our setting, no prior studies were conducted in the study area. So, this study aimed to assess the magnitude and associated factors of neonatal sepsis among neonates admitted to the neonatal intensive care unit at Hawassa University Comprehensive Specialized Hospital, Sidama Regional State, Ethiopia. Methods A hospital-based cross-sectional study was carried out among 287 neonates from March 1, 2020, to April 25, 2020. An interviewer-administered structured questionnaire was used to collect the data. The data were cleaned, coded, and entered into Epi Data 3.1 software and exported to Statistical Package for Social Science (SPSS) software version 23.0 for analysis. Binary logistic regression analyses were performed to identify variables having a significant association with neonatal sepsis. A p-value of ≤ 0.05 was considered statistically significant during multivariable logistic regression. Results The study found that the magnitude of neonatal sepsis was 56%. The mean age of neonates was 3.2(SD±2.2) days. Around two-fifths (39%) of neonates were in the gestational age of <37 completed weeks. A quarter of mothers(25.8%) were delivered through cesarean section. During labor, 251 (87.5%) mothers had ≤4 digital vaginal examinations. Moreover, the finding revealed that mothers who delivered by cesarean section [AOR = 2.13, 95% CI (1.090-4.163)]. neonates who had been resuscitated at birth [AOR = 4.5, 95% CI (2.083-9.707)], and neonates who had NG tube inserted [AOR = 4.29, 95% CI (2.302-8.004)] were found to be significantly associated with neonatal sepsis. Conclusions The current study shows that neonatal sepsis was prevalent among more than half of the neonates admitted to the NICU. Therefore, designing strategies to enhance the aseptic techniques of professionals in the provision of care and actively and collaboratively working with cluster health facilities is highly recommended.